2022
DOI: 10.1093/europace/euac118
|View full text |Cite
|
Sign up to set email alerts
|

Current status of reimbursement practices for remote monitoring of cardiac implantable electrical devices across Europe

Abstract: Remote monitoring (RM) of cardiac implantable electrical devices (CIEDs) is currently proposed as a standard of care for CIEDs follow-up, as recommended by major cardiology societies worldwide. By detecting a series of relevant device and patient-related parameters, RM is a valuable option for early detection of CIEDs' technical issues, as well as changes in parameters related to cardio-respiratory functions. Moreover, RM may allow longer spacing between in-office follow-ups and better organization of in-hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…In this analysis, we observed a huge gap in the implementation of remote monitoring; Polish patients were approximately a third as often controlled with remote monitoring compared with other regions. This could be at least partially explained by significant heterogeneity in reimbursement policies across Europe [ 20 ]. An analysis of the baseline characteristics revealed that over 50% of study participants were enrolled in France, Germany and Spain, countries with wide reimbursement policies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this analysis, we observed a huge gap in the implementation of remote monitoring; Polish patients were approximately a third as often controlled with remote monitoring compared with other regions. This could be at least partially explained by significant heterogeneity in reimbursement policies across Europe [ 20 ]. An analysis of the baseline characteristics revealed that over 50% of study participants were enrolled in France, Germany and Spain, countries with wide reimbursement policies.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of the baseline characteristics revealed that over 50% of study participants were enrolled in France, Germany and Spain, countries with wide reimbursement policies. Contrary to that, there is a lack of remote monitoring reimbursement in Poland, which is one of the primary barriers for its wider implementation [ 20 , 21 ]. Of note, almost a quarter of Polish patients wanted to learn more about the remote monitoring of an ICD.…”
Section: Discussionmentioning
confidence: 99%
“…Such remote monitoring will involve privacy matters and cybersecurity concerns 75 . Reimbursement considerations of remote monitoring varies greatly in developed countries, 76 and will likely lead to new costs to support reuse of CIEDs in LMICs.…”
Section: Beyond Advocacymentioning
confidence: 99%
“…Third, there is significant worldwide heterogeneity in the reimbursement for RM 86,189,195 . In Europe, many clinics receive no reimbursement for RM, and this has been identified as a major barrier to the use and expansion of RM 86,195 .…”
Section: Section 15 Knowledge Gaps and Future Needsmentioning
confidence: 99%
“…86,189,195 In Europe, many clinics receive no reimbursement for RM, and this has been identified as a major barrier to the use and expansion of RM. 86,195 Uptake of RM has slowed in parts of the Asia-Pacific region, with a lack of reimbursement identified as a barrier in many locales. 189 Finally, a larger shift may be needed in how we think about RM of CIEDs.…”
Section: Reimbursement Reform For Remote Monitoringmentioning
confidence: 99%